PENGEMBANGAN MEDIA PENGAYAAN PERMAINAN ULAR TANGGA BERBASIS GOOGLE SLIDE PADA MATERI AKAD MUDHARABAH, MUSYARAKAH DAN MURABAHAH KELAS XI SMK NEGERI 2 MOJOKERTO - Fana Ardiana, Lian Rahim; Listiadi, Agung (Inspiratif Pendidikan, 2023)
The purpose of this study was to produce a game of snakes and ladders based on Google Slides as a medium of enrichment in the material for class XI mudharabah, musyarakah, and murabahah contracts at SMK Negeri 2 Mojokerto which was tested suitable for use in enrichment activities and received positive responses from students. The development model used is the 4D development model (Define, Design, Develop and Disseminate) from Thiagarajan. The development process is carried out according to the stages of the 4D development model, namely through the definition stage, design stage, and development stage. The deployment stage is not carried out. After the development process follows the existing stages, an assessment activity is carried out on Google Slides. To assess the feasibility of the developed media, the expert carried out review and validation activities as well as limited trial activities for 15 students.validation of the development of the snake and ladder game enrichment media based on Google Slides from material experts and media experts with an average percentage of 93.55% and 95.15% with very feasible criteria. While the results of the trial for students obtained an average value of 90.48% with the criteria of very understanding. Thus, it can be concluded that the enrichment media for the game of snakes and ladders based on Google Slides in the material for the class XI mudharabah, musyarakah, and murabahah contracts is very appropriate to be used as an enrichment medium in schools.